Perbandingan Adverbia Perulangan “Zai” dan “You” dalam Bahasa Mandarin dengan Adverbia Perulangan dalam Bahasa Indonesia - Melisa, Melisa; Asihin, David Hartono Asihin; Ng, Yuliandre Wijaya Ng; Wijaya, Kesumawaty Wijaya; Wijaya, Darmawan Wijaya (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The repetitive adverbs “Zai” and “You” in Mandarin have the same meaning when translated into Indonesian, namely “Lagi”. Because language is universal and unique, this study was conducted with the aim of explaining the similarities and differences in the use and structure of the repetitive adverbs “Zai” and “You” in Mandarin with the word “Lagi” in Indonesian. This study was designed with a qualitative descriptive research design. The data collection technique used documentation techniques and the data sources were sentences that used the words “Zai” and “You” in Mandarin with the word “Lagi” in Indonesian. The theories used in this study are the theory of universality of language and uniqueness of language as well as contrastive analysis to examine the similarities and differences of the three words based on the definition, position or use of the words. The results of the study showed that there were 4 similarities, consisting of 1 similarity in definition, 3 similarities in terms of usage, and 7 differences, consisting of 2 differences in terms of structure and 5 differences in terms of usage in the repetitive adverbs